2014
DOI: 10.1016/j.gca.2013.06.018
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical constraints on the effects of pH, salinity, and temperature on clumped isotope signatures of dissolved inorganic carbon species and precipitating carbonate minerals

Abstract: The use of carbonate 'clumped isotope' thermometry as a geochemical technique to determine temperature of formation of a carbonate mineral is predicated on the assumption that the mineral has attained an internal thermodynamic equilibrium. If true, then the clumped isotope signature is dependent solely upon the temperature of formation of the mineral without the need to know the isotopic or elemental composition of coeval fluids. However, anomalous signatures can arise under disequilibrium conditions that can … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
208
10
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 145 publications
(231 citation statements)
references
References 92 publications
12
208
10
1
Order By: Relevance
“…The offset of 0.03 ‰ between aragonite and calcite is at the lower end of what we observe. A recent theoretical modeling effort (Hill et al, 2014) has produced similar predicted 47 values for aragonite and calcite although with more depleted (less agreement) values between predicted and observed aragonite 47 and a smaller offset between aragonite and calcite.…”
Section: Comparison With Theoretical Predictionsmentioning
confidence: 95%
See 2 more Smart Citations
“…The offset of 0.03 ‰ between aragonite and calcite is at the lower end of what we observe. A recent theoretical modeling effort (Hill et al, 2014) has produced similar predicted 47 values for aragonite and calcite although with more depleted (less agreement) values between predicted and observed aragonite 47 and a smaller offset between aragonite and calcite.…”
Section: Comparison With Theoretical Predictionsmentioning
confidence: 95%
“…Theoretical modeling of 63 for different carbonate minerals Hill et al, 2014;Tripati et al, 2015) has been combined with theoretical acid digestion fractionations to give predicted 47 values for a variety of carbonate minerals. These predictions generally agree with measured inorganic and biogenic studies; however, they are more depleted in 47 for a given temperature.…”
Section: Comparison With Theoretical Predictionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Additional hypotheses have been advanced, including reaction temperature, acid quality (Zaruur et al, 2013), precipitation method for the carbonates, solution pH, or disequilibrium during precipitation (Hill et al, 2014). Three recent studies, however, have changed this view.…”
Section: The Absolute Reference Framementioning
confidence: 99%
“…In other words, the dispersion observed in Figure 1 might also partly reflect some true (i.e., not due to measurement and/or data treatment bias) characteristics of the carbonate clumped isotope systematics as for example: i/ isotopic disequilibrium of 13 C-18 O clumping (as observed by Affek et al, 2008;Daëron et al, 2011;Saenger et al, 2012); ii/ ∆ 47 vital effects for some biogenic minerals; iii/ variations in 13 C-18 O clumping distribution with the structure or chemical compositions of the carbonate either inside the mineral lattice (as suggested by Schauble et al, 2006, Hill et al, 2014 or into CO 2 generated by H 3 PO 4 acid digestion (as suggested by Guo et al, 2009)]. Such "material-specific explanations" for the dispersion of ∆ 47 data in Figure 1 for siderite in Fernandez et al, (2014) or carbonate groups in phosphate ; e.g., Eagle et al, 2010).…”
mentioning
confidence: 98%